Development of walking robot using compliance mechanism - Chua, Wei Ming; Khairul Fikri, Muhammad (Penerbit UMP, 2021)
Walking robot is a trend in this 21st century as Industrial Revolution 4.0 which involved automation has become a hot topic. Unlike ordinary moving robots, walking robots that take humans and animals as references can move on unpaved surfaces. Compliance mechanism is a flexible mechanism that transfers input force into output force through plastic deformation of certain members in the structure. A compliant structure can be classified as a monolithic structure that deforms elastically without any joint or linkage between the members. Unlike motorised robot legs requiring an input motion in each joint and link, a single input force can operate a compliant leg. Therefore, this research aims to develop a 3D printed compliant leg. This project is challenging because there is no reference for the single-piece compliant leg development using Three-Dimensional(3D) printing technology. The application of Jansen Linkage in the development of the compliant leg also results in difficulties because there is no standard equation for the calculation of each member in the Jansen Linkage. Hence, the development of the Jansen Linkage using different dimensions will solve these problems by varying the difference occurring upon changing the dimension. We also make Finite Element Analysis (FEA) of the product. The thesis will be supported by the walking motion pattern, force vs time graph and FEA analysis results for the product.